"ROOTED EXPRESSIONS: EXPLORING THE USAGE OF IDIOMS WITH PHYTONYMIC COMPONENTS" - Bektosh Norbo’tayevich Tursunboev (Western European Studies, 2025)
This article delves into the symbiotic relationship between language and nature, particularly focusing on idioms enriched with phytonymic components—expressions derived from the names of plants. The exploration seeks to unravel the roots of these idioms and illuminate their versatile usage in everyday communication. Beyond the botanical sense of a plant producing edible outcomes, the metaphorical interpretation is emphasized.
Keywords: language and nature; symbiotic relationship